The Economic Consequences of Covid-19 in Africa Particularly in Senegal - Omar Ndao, El Hadji; Gbodossou, Flora (Issues in Social Science, 2024)
China has become rapidly the crossroad of the world’s trade. The country is even commonly called the world’s factory. Because of that, what affects China, has necessarily an impact in many other parts of the globe. Since December 2019, Covid-19 is impacting on all continents, bringing tremendous economic consequences. Many sectors have been touched and countries are actively trying to take actions in order to minimize damages. West Africa has suffered from the negative economic impacts of Covid-19, particularly Senegal. This paper shows the decreasing on imports and exports for main goods like oil, gas, foods…